Combined Treatment with Antiviral Therapy and Rituximab in Patients with Mixed Cryoglobulinemia: Review of the Literature and Report of a Case Using Direct Antiviral Agents-Based Antihepatitis C Virus Therapy. (1st March 2015) - Urraro, Teresa; Gragnani, Laura; Piluso, Alessia; Fabbrizzi, Alessio; Monti, Monica; Fognani, Elisa; Boldrini, Barbara; Ranieri, Jessica; Zignego, Anna Linda
Abstract : Mixed cryoglobulinemia (MC) is an autoimmune/B-cell lymphoproliferative disorder associated with Hepatitis C Virus (HCV) infection, manifesting as a systemic vasculitis. In the last decade, antiviral treatment (AT) with pegylated interferon (Peg-IFN) plus ribavirin (RBV) was considered the first therapeutic option for HCV-MC. In MC patients ineligible or not responsive to antivirals, the anti-CD20 monoclonal antibody rituximab (RTX) is effective. A combined AT plus RTX was also suggested. Since the introduction of direct acting antivirals (DAAs), few data were published about MC and no data about a combined schedule. Here, we report a complete remission of MC after a sustained virological response following a combined RTX/Peg-IFN+RBV+DAA (boceprevir) treatment and review the literature about the combined RTX/AT.